Research Patterns in Formative Assessment: A Bibliometric Review of Primary and Secondary School Studies - Saky, Sheikh Abu Toha Md; Inayati, Nurul Latifatul; Islam, Md Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study examines the evolving landscape of formative assessment in primary and secondary education through bibliometric analysis, emphasizing theoretical foundations, technological integration, and global applications. A total of 398 documents from the Scopus database (1997–2024) were analyzed using Biblioshiny for R, with an annual growth rate of 14.74%. Key metrics such as keyword co-occurrence, thematic clusters, and global collaboration networks were evaluated to identify prevailing research trends and gaps. The results highlight significant themes, including feedback mechanisms, self-assessment, peer assessment, and the integration of digital technologies like e-learning, gamification, and artificial intelligence. Collaboration patterns reveal the USA, China, and Germany as research hubs, while Southeast Asia demonstrates regional efforts. However, barriers such as inconsistent definitions, limited teacher training, and technological inequities persist. This study contributes novel insights by bridging critical gaps in the literature, particularly the lack of cultural perspectives and underexplored non-traditional educational contexts. It combines bibliometric analysis with thematic insights to illuminate the transformative potential of formative assessment across diverse educational settings. Educators and policymakers can use these findings to develop regionally tailored strategies for formative assessment, addressing implementation challenges and promoting effective practices globally. By fostering personalized learning and equitable access, formative assessment supports inclusive education, narrowing disparities across various learner demographics.